Castañón Cheiloplasty: a viable and effective technique in the partial reconstruction lower lip - Leodanyi Adán Socarrás (Editorial Ciencias Médicas, 2022)
Introduction: For the treatment of labial squamous cell carcinoma there are several therapeutic modalities, but surgery is the first choice. Numerous techniques have been described for the management of lesions affecting more than a third of the lower lip. However, the selection of any particular one depends on the fulfillment of the reconstructive principles of this unit. Objective: Exemplify the benefits of using Castañón cheiloplasty for partial lip reconstruction in a patient with squamous cell carcinoma of the lower lip. Case presentation: A 68-year-old male patient with a history of smoking and alcoholism was presented, who went to the Head and Neck Oncological Surgery consultation for presenting a lesion located in vermilion of the lower lip. An incisional biopsy reported moderately differentiated squamous cell carcinoma. It was studied as a T2N0M0, stage II and was treated surgically by subtotal cheilectomy and reconstruction with Castañón technique. Conclusions: The clinical case of a patient with squamous cell carcinoma of the lower lip, a pathological entity of high incidence, was presented. Surgery was the only treatment modality used. Once the surgical resection of the lesion was performed, the defect was reconstructed, for which the cheiloplasty described by Castañón was used, a useful option to achieve compliance with the aesthetic and functional principles.